Sistem Pendukung Keputusan berbasis Vikor untuk Penyaluran Gas Lpg 3 Kg Bersubsidi - Rahmadani, Nadhilla; Fauziah, Rizky; Mardalius, Mardalius (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
PT. Citra Gas Nusantara always has difficulty in determining priority bases and has not done so objectively or still does so manually. So that in this condition it has an impact on uneven distribution that does not match the needs of the community. The purpose of this study is to create a decision support system for selecting priority LPG Gas bases based on VIKOR. The research method used is the waterfall method, which consists of the analysis, planning, implementation, and testing processes. Only 10 alternatives out of 31 alternative choices are used in the calculation, because only 10 alternatives are included in the priority base criteria based on four criteria: cylinder ownership, customers, discipline, and accuracy of Brimola transactions. The results of our findings are in the form of a decision support system for selecting priority bases for the distribution of 3 Kg LPG Gas which is realized in the form of a website. The results of the VIKOR technique calculation for the Aminuddin base obtained the lowest score of 0, so in this case, the Aminuddin Base is the base that must be prioritized for distribution. In VIKOR, the lowest value is the best compromise solution or the best alternative that is ranked first. The results of the black box test starting from login, the menu on the main page and logout also show that the system can run as expected and will also have an impact on increasing efficiency and effectiveness in the distribution of subsidized 3 Kg LPG Gas